Advances in stem cell research for the treatment of male sexual dysfunctions. Issue 2 (March 2016) - Soebadi, M. Ayodhia; Moris, Lisa; Castiglione, Fabio; Weyne, Emmanuel; Albersen, Maarten
Abstract : Purpose of review: To summarize recent literature on basic stem cell research in erectile dysfunction in cavernous nerve injury, aging, diabetes, and Peyronie's disease and to provide a perspective on clinical translation of these cellular therapies. Recent findings: Stem cell research has been concentrated on mesenchymal stem (stromal) cells from bone marrow and adipose tissue. Application of both cell types has produced positive effects on erectile function in various animal models of erectile dysfunction. In acute animal models, such as cavernous nerve injury-induced erectile dysfunction and chemically induced Peyronie's disease, engraftment and differentiation have not been observed, and stem cells are believed to interact with the host tissue in a paracrine fashion, whereas in chronic disease models some evidence suggests both engraftment and paracrine factors may support improved function. Clinical trials are now investigating therapeutic efficacy of cellular therapy, whereas the first safety studies in humans have recently been published. Summary: Evidence from preclinical studies has established stem cells as a potential curative treatment for erectile dysfunction and early phase clinical trials are currently performed.